Polish Independent Press Summary, no. 59 (1989) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Przegląd Wiadmości Agencyjnych, no. 195 (7 July 1989). Extract from Przegląd Wiadmości Agencyjnych, no. 196 (14 July 1989). Extract from Przegląd Wiadmości Agencyjnych, no. 197 (21 July 1989). Extract from Wolny Głos Nauczycielski, no. 75 (June 1989). Extract from Świat, no. 8 (10 July 1989). Table of Contents from Kultura Niezależna, no. 51 (May 1989). Cover Page from Żakowski, Jacek. Anatomia Smaku czyli Rozmowy o losach zespołu Tygodnika Powszechnego w latach 1953-1956. Warszawa: Most, 1988. Cover Page from Ngor, Haing. Kambodżańska Odyseja: Dokument. Warszawa: Pomost, 1989. Cover Page from Krajobraz po Szoku. Warszawa: Przedświt, 1989. Extract from Krajobraz po Szoku. Warszawa: Przedświt, 1989.